New record of Spotstripe snapper, Lutjanus ophuysenii (Perciformes: Lutjanidae) from Korea - Han Na Kim (Fisheries and Aquatic Sciences, 2016)
Abstract Three specimens of Lutjanus ophuysenii (217.8–226.7 mm in standard length) were collected by a gill net at Korea between August 2015 and July 2016. This species has not previously been recorded from Korea. L. ophuysenii is very similar to Lutjanus vitta. But several morphological characteristics distinguish the two species, including the number of lateral line scales (46–49 scales in L. ophuysenii; 49–52 scales in L. vitta), a black spot in the middle part of the longitudinal stripe (present in L. ophuysenii; absent in L. vitta), and the absence of a scale on posterior end of the preopercle in L. ophuysenii (present in L. vitta). The Korean name proposed for L. ophuysenii is “Jeom-jul-tung-dom.”